Investigating the deformation behavior of hot-pressed Ti/Al/Ti laminated composite. (9th June 2023) - Assari, Amir Hossein
Abstract: In this paper, the deformation behavior of Ti/Al/Ti composite fabricated by the hot-pressing process was investigated by simulation and experimental analyses. Furthermore, the elastic properties of laminated composites were predicted by using different representative volume elements (RVEs) subjected to compression and tension. The SEM images displayed well-bonded straight interfaces. Also, XRD and EDS analyses revealed that TiAl3 was the only intermetallic compound that grew at the Ti/Al interfaces. The simulation results showed that stress concentration and strain localization existed at the interfaces during hot compression. In addition, the elastic behavior of simulated RVEs agreed relatively well with the experimentally-obtained values. Nevertheless, the predicted values of effective elastic constants of large RVE were consistent with the experimental values. This is due to the actual thickness, volume fraction, and stacking order of composite layers. Highlights: The finite element simulation of hot-pressing process was conducted. Two sizes of representative volume element (RVE) simulated the deformation behavior of Ti/Al/Ti laminated composite. The stress concentration and strain localization occurred at metal/intermetallic interfaces. Experimental stress-strain results matched well with the predicted findings.